Discrimination through the male genitalia of the sub genera ~fBombus Latreille s. 1. and Psithyrus Lepeletier s. 1. living in Italy (Hymenoptera Apidae Bombinae) (Bollettino di zoologia agraria e bachicoltura, 2024)
The study examined and discussed the morphology and variability of male genitaliain the Bombinae subfamily, with a comparison of the nomenclature used byformer Authors. The characteristics of the considered apparatus have been usedto draw up a dichotomic key of the subgenera of Psithyrus Lepeletier s.l. andBombus Latreille s.l. which can be found in Italy, accompanied by SEM-photosof each subgenus.
Keywords: male genitalia; Bombus; Psithyrus; Italy